Shear strength behaviour of sugarcane bagasse reinforced soils - Oderah, Vincent (Department of Civil Engineering, 2016)
Sugarcane is considered as the most abundant plant based crop grown in the tropics and part of the temperate climates. Its by-product, sugarcane bagasse, constitutes 30% of the total production. In the past, it was considered as waste material but contemporaries through innovative research projects over the years have found uses for it. Among these projects is soil reinforcement, which provides an alternative application to industrial by-products and natural fibres as a way of reducing their environmental footprints and contributing to sustainable geotechnics. Although bagasse morphological composition contains structural elements ideal for reinforcement and composite materials, it has received little research as a standalone reinforcement material. Because of this, a direct shear test was therefore initiated to establish the usefulness of using sugarcane bagasse as a soil reinforcement material by comparing the extent of shear strength and stiffness response due to its inclusion to unreinforced soil. Three different types of bagasse, fibre, millrun and pith, were added to unreinforced soil in percentage by weight content of 0.3 - 1.7. The bagasse was added to Klipheuwel sand, Cape Flats sand and Kaolin Clay at both dry and moist conditions. In addition, durability studies involving 12 cycles of wetting and drying, and soaking for a period of 14 days were constituted.